Can lab and field testing be complementary in defining physiological effort through the Serra da Estrela routes? - Bartolomeu, RF.; Bragada, JA.; Casanova, N.; Casanova, J.; Costa, MJ. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
Background: The current classification of the hiking trails using an agreement between lab and field test is inexistent. The aim of this study was to characterize a single route in a physiological basis. Methods: Twenty-nine subjects underwent a 11km hike. The velocity and heart rate (HR) were monitored continuously. In a separate day, all subjects underwent a laboratory test to measure both HR and Oxygen uptake (VO2). Linear regressions between net HR (HRnet) vs %VO2 reserve were computed. Results: The mean coefficients of determination were very high (R2=0.98). The calculated %VO2reserve mean values for this route were 42%. Conclusions: This route elicited light-to-moderate intensities. When hiking in this or in similar round routes, the formula %VO2reserve=0.64+0.77*HRnet can be used to assess the hiking intensity. The complementarity of the field and lab tests proved to be useful and reliable in defining the energetic demands of the hike. Funding: Foundation for Science and Technology (FCT) of Portugal (POCI-01-0145-FEDER-023604).